1994
DOI: 10.1007/bf00019490
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of transgenic potato plants expressing an antisense granule-bound starch synthase gene: increase of the antisense effect during tuber growth

Abstract: Transgenic plants of a tetraploid potato cultivar were obtained in which the amylose content of tuber starch was reduced via antisense RNA-mediated inhibition of the expression of the gene encoding granule-bound starch synthase (GBSS). GBSS is one of the key enzymes in the biosynthesis of starch and catalyses the formation of amylose. The antisense GBSS genes, based on the full-length GBSS cDNA driven by the 35S CaMV promoter or the potato GBSS promoter, were introduced into the potato genome by Agrobacterium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 41 publications
(46 reference statements)
2
25
0
Order By: Relevance
“…Also in potato it was reported that the values of mRNA in antisense and co-suppression transformants varied, and was different within one tuber and different tubers from the same clone. The only relation which could be found was that in all antisense plants the level of mRNA was always lower than in the controls (Kuipers et al 1995;Flipse et al 1996). This was also observed in cassava.…”
Section: Discussionsupporting
confidence: 51%
“…Also in potato it was reported that the values of mRNA in antisense and co-suppression transformants varied, and was different within one tuber and different tubers from the same clone. The only relation which could be found was that in all antisense plants the level of mRNA was always lower than in the controls (Kuipers et al 1995;Flipse et al 1996). This was also observed in cassava.…”
Section: Discussionsupporting
confidence: 51%
“…Northern analysis RNA was isolated according to Kuipers et al (1994b), fractionated by electrophoresis, blotted and hybridised to the cDNA for potato GBSSI, as described by Sambrook et al (1989). A 24S rRNA probe was used as a standard (Landsmann et al 1985).…”
Section: Pcr Analysismentioning
confidence: 99%
“…Expression of the antisense GBSS gene using the GBSS promoter resulted in a higher stability for the amylosefree trait than with the 35S promoter (Visser et al 1991). Field analyses of these transgenic plants indicated that inhibition of GBSS gene expression could be achieved without significantly affecting the starch or sugar content of tubers (Kuipers et al 1994). The amylosefree trait in transgenic plants showed a dominant Mendelian inheritance, so the genetically modified amylose-free potato clones have use as either male or female progenitors in a breeding program (Heeres et al 1997).…”
Section: Amylose-free Starchmentioning
confidence: 99%
“…Candidate genes located in the QTL regions affecting the dry matter content include two starch phosphorylase genes on chromosome I, a Rubisco gene on chromosome II, a starch synthase gene on chromosome III, a starch phosphorylase gene and a debranching enzyme gene on chromosome IX, a Rubisco activase gene and an apoplast invertase gene on chromosome X, a sucrose transporter gene on chromosome XI, and a sucrose synthase gene on chromosome XII (Chen et al 2001). Transgenic evidence for the involvement in starch dry matter has been available for several of these enzymes, including sucrose synthase (Zrenner et al 1995), starch synthase (Kuipers et al 1994), and glucan branching enzyme (Kortstee et al 1996). Some of the genes have already converted to molecular markers for markerassisted selection of dry matter content of potato tubers.…”
Section: Molecular Genetic Maps and Markers Of Dry Matter Contentmentioning
confidence: 99%
See 1 more Smart Citation